Pain Management and Life Satisfaction in Elderly Individuals: A Single Centred Study - Ozer, Zulfunaz; Turan, Gulcan Bahcecioglu; Atan, Gulden (Marmara Univ, Inst Health Sciences, 2021)
Objective: This study was conducted to find out the pain management status and life satisfaction of elderly individuals living in a nursing home and to determine the relationship between these. Methods: This descriptive cross-sectional study was conducted in a nursing home in Turkey in November 2019. The data were collected by the researchers with face-to-face interview technique by using Personal Information Form, Geriatric Pain Measure (GPM), Pain Management Inventory (PMI) and Life Satisfaction Scale (LSS). Results: GPM total score was 48.95 +/- 11.24, and average LSS was 14.37 +/- 6.85. There is a positive statistically significant association between GPM and PMI (r=0.385; p<0.01), while there is a negative statistically significant association between GPM and LSS (r=-0.369; p<0.01). There is a negative statistically significant association between PMI and LSS (r=-0.344; p<0.01). Conclusion: It was found that elderly individuals had moderate level of pain and poor life satisfaction. It was found that as level of pain increased, elderly individuals' life satisfaction decreased.
Keywords: Pain; Life Satisfaction; Elderly Nursing Home